DEVELOPMENT OF ECONOMIC RELATIONS AND THE PRACTICE OF THE SUPREME COURT: CONNECTION AND INTERACTION - Khotsianovska, Natalia; Dzhuglya, Tetiana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: the article is devoted to a direct consideration of the issue of the relationship between the Supreme Court’s practice and the development of economic relations of Ukraine and their interaction. Research methods: the article uses the dialectical method of cognition, general scientific methods and special research methods. In particular, the structural and function method, deductive method and the method of scientific forecasting. Results: the article outlines the peculiarities of the economic relations of Ukraine at the present stage of development due to the focus on European integration; identifies the factors that influence the development of economic relations in terms of traditional approaches and modern scientific research; revealed that the quality of the judicial system is one of the factors that influence the development of economic relations; identifies that the quality of the judicial system is one of the factors influencing the development of economic relations at the present stage, and the practice of the Supreme Court plays a significant role in the development of economic relations under martial law; emphasises the role of legal positions of the Supreme Court as a guideline for law enforcement in the context of uncertainty of certain economic relations arising from military operations on the territory of Ukraine; identifies the importance of the Supreme Court’s legal opinions for the formation of the unity of judicial practice and its generalisation for a unified approach to the regulation of economic relations at the current stage, which can serve as a guide for persons who have problems with implementation legal norms in economic relations under conditions of martial law. Discussion: approaches to determining the factors influencing the development of economic relations at the present stage in Ukraine, the importance of the Supreme Court’s practice in regulating economic relations and their development at the present stage in general and the areas most in need of such influence.